About the Concept “Learning” in Russian-language Academic Discourse - M. A. Ivanova (Высшее образование в России, 2021)
Being one of the basic didactic terms, “learning” is frequently translated by Russianspeaking researchers as either “obuchenie” or “uchenie”. It seems strange, as these two words are not synonyms in Russian. Moreover, in Russian conventional didactics they denote two different phenomena: “obuchenie” refers to the entire educational process consisting of both the teacher’s and the learner’s activities while “uchenie” corresponds to the latter one. Successful international academic communication presupposes that any terms accepted by English-speaking professionals should be adapted to the national didactic concepts of this or that country. Taking this requirement into account, the author concludes that the only possible equivalent of “learning” in Russian is “uchenie”, not “obuchenie”, while the phrase “the shift from teaching to learning” and the term “student-centred learning” should be translated as “sdvig / perekhod ot prepodavaniya k ucheniyu” and “studentotsentrirovannoe uchenie” respectively. The author comes to the conclusion that student-centred learning (SCL) opposed to student-centred teaching can be considered the highest point in the development of student-centred approach currently prevailing in European countries. SCL as a new type of learning means that the student becomes an active participant in educational process having his (her) own needs and interests in the focus of attention. The substitution of the word “uchenie” by the incorrect variant “obuchenie” existing in the Russian academic discourse nowadays prevents Russian-speaking researchers from seeing clearly the essence of SCL.